Encyclopedia of Polymer Science and Technology 2004
DOI: 10.1002/0471440264.pst451
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Plastics

Abstract: We discuss methods of prediction of long‐term performance and reliability of polymer‐based materials from short‐term tests. The methods include prediction of slow crack propagation and also predictions based on correspondence principles including the stress–time correspondence. The amount of experimentation needed for reliable predictions is much lower than generally believed. For instance, experiments at two stress levels for a four‐phase polymer liquid crystal are sufficient for creation of a master curve. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The glass transition temperature (T g ) was taken as the midpoint of the change of heat capacity increment ("C p /2) associated with the glass-rubber transition. The specific heat increment "C p associated with T g of amorphous phase of semicrystalline PTT, was calculated from the vertical distance between two extrapolated baselines at the glass transition temperature according to the literature [32]. The nominal melting temperature (T m ) was defined as the of peak of the melting endo therm during heating from 25 to 250°C, and the nominal crystallization temperature (T c ) was defined as the peak of the crystallization exotherm upon cooling from 250 to -25°C.…”
Section: Characterization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glass transition temperature (T g ) was taken as the midpoint of the change of heat capacity increment ("C p /2) associated with the glass-rubber transition. The specific heat increment "C p associated with T g of amorphous phase of semicrystalline PTT, was calculated from the vertical distance between two extrapolated baselines at the glass transition temperature according to the literature [32]. The nominal melting temperature (T m ) was defined as the of peak of the melting endo therm during heating from 25 to 250°C, and the nominal crystallization temperature (T c ) was defined as the peak of the crystallization exotherm upon cooling from 250 to -25°C.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…using the bending mode at a frequency of 1 Hz, and at a heating rate of 3°C/min from -100 to 250°C. The glass transition temperature was taken as the temperature at the maximum !-relaxation peak of the loss modulus E# and tan # curves [32]. The tensile tests were performed on an Instron 1112 tensile testing machine (Norwood, MA,USA) at room temperature.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Nelson (41) has reported that these transitions can be related to vibration damping. This is also true for acoustical damping (42). In both of this cases, the strength of the beta transition is taken as a measurement of how effectively a polymer will absorb vibrations.…”
Section: Sub-t G Transitionsmentioning
confidence: 99%
“…An improvement of the attraction between the polymer and the aggregates can also be achieved by adding a coupling agent such as silane to the monomer. This lowers the extent of pore formation and causes a decrement in stiffness [11]. Our main interest consists in grafting polymers onto aggregates surfaces.…”
Section: Introductionmentioning
confidence: 99%